Allelic variation in rice Fertilization Independent Endosperm 1 contributes to grain width under high night temperature stress. Issue 1 (23rd September 2020) - Dhatt, Balpreet K.; Paul, Puneet; Sandhu, Jaspreet; Hussain, Waseem; Irvin, Larissa; Zhu, Feiyu; Adviento‐Borbe, Maria Arlene; Lorence, Argelia; Staswick, Paul; Yu, Hongfeng; Morota, Gota; Walia, Harkamal
Summary: A higher minimum (night‐time) temperature is considered a greater limiting factor for reduced rice yield than a similar increase in maximum (daytime) temperature. While the physiological impact of high night temperature (HNT) has been studied, the genetic and molecular basis of HNT stress response remains unexplored. We examined the phenotypic variation for mature grain size (length and width) in a diverse set of rice accessions under HNT stress. Genome‐wide association analysis identified several HNT‐specific loci regulating grain size as well as loci that are common for optimal and HNT stress conditions. A novel locus contributing to grain width under HNT conditions colocalized with Fie1, a component of the FIS‐PRC2 complex. Our results suggest that the allelic difference controlling grain width under HNT is a result of differential transcript‐level response of Fie1 in grains developing under HNT stress. We present evidence to support the role of Fie1 in grain size regulation by testing overexpression (OE) and knockout mutants under heat stress. The OE mutants were either unaltered or had a positive impact on mature grain size under HNT, while the knockouts exhibited significant grain size reduction under these conditions.